Red dot design yearbook. - Zec, Peter, 1956- (Essen : Red dot.)
The yearbook volumes "Living", "Doing" and "Working" are a must for anyone interested in remaining up-to-date on the current trends in international product design: architects, designers, product and purchasing managers, design institutes, technology freaks, design-scene insiders, and individuals who are fascinated by culturally relevant product development. The volume titled "living" presents furniture, household items, cooking utensils, lamps, garden tools, sanitary installations, office furniture and accessories, while the volume "doing" displays products from activity- and technology-oriented categories, such as sporting goods, computers, telephones, tools and instruments, and medical equipment, as well as cars and other vehicles of transportation.
Keywords: Industrieel ontwerpen